Utilization of Adobe Creative Cloud Media to Support Project-Based Learning for Internship Students in the Digitaliz Unit at the Hasnur Centre Foundation - Azumaradhi Adzra; Mastur Mastur; Agus Hadi Utama (PT ARRUS Intelektual Indonesia, 2024)
Adobe Creative Cloud is a comprehensive suite of applications offering advanced tools for graphic design, video editing, animation, photography, and web development. This study aims to explore the utilization of Adobe Creative Cloud in supporting project-based learning (PjBL) at Hasnur Centre Foundation. The research method used is descriptive qualitative research, which includes observation, interviews, and documentation during the internship program held from February 28 to March 17, 2024. The internship program involved 61 students from Global Islamic Boarding School, who used various Adobe Creative Cloud applications such as Premiere Pro, After Effects, and Audition in their projects. The results showed that the use of Adobe Creative Cloud enhanced students' creativity, collaboration, and material understanding. In conclusion, Adobe Creative Cloud is effective in supporting PjBL and increasing student motivation.